2018
DOI: 10.3389/fncel.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RhoA-Subfamily GTPases Suppresses Schwann Cell Proliferation Through Regulating AKT Pathway Rather Than ROCK Pathway

Abstract: Inhibiting RhoA-subfamily GTPases by C3 transferase is widely recognized as a prospective strategy to enhance axonal regeneration. When C3 transferase is administered for treating the injured peripheral nerves, Schwann cells (SCs, important glial cells in peripheral nerve) are inevitably impacted and therefore SC bioeffects on nerve regeneration might be influenced. However, the potential role of C3 transferase on SCs remains elusive. Assessed by cell counting, EdU and water-soluble tetrazolium salt-1 (WST-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Rho GTPases: small GTPases of the Rho (e.g., Cdc42, RhoA, Rac1) and Ras (RalA, RalB) families act as molecular switches, shuttling between activated GTP-bound and inactive GDP-bound states. Rho and Ras GTPases regulate cytoskeletal organization in Schwann cells to modulate critical events such as radial sorting during development (Benninger et al, 2007 ; Guo et al, 2013 ; Tan et al, 2018 ; Ommer et al, 2019 ). The chronic lack of Ral proteins in Schwann cells impairs radial sorting, resulting in the formation of unmyelinated or hypo-myelinated large-caliber axons, and abnormalities in the myelin sheath (Ommer et al, 2019 ).…”
Section: Schwann Cells: Understanding Development To Engineer Repairmentioning
confidence: 99%
“…Rho GTPases: small GTPases of the Rho (e.g., Cdc42, RhoA, Rac1) and Ras (RalA, RalB) families act as molecular switches, shuttling between activated GTP-bound and inactive GDP-bound states. Rho and Ras GTPases regulate cytoskeletal organization in Schwann cells to modulate critical events such as radial sorting during development (Benninger et al, 2007 ; Guo et al, 2013 ; Tan et al, 2018 ; Ommer et al, 2019 ). The chronic lack of Ral proteins in Schwann cells impairs radial sorting, resulting in the formation of unmyelinated or hypo-myelinated large-caliber axons, and abnormalities in the myelin sheath (Ommer et al, 2019 ).…”
Section: Schwann Cells: Understanding Development To Engineer Repairmentioning
confidence: 99%
“…Therefore, inhibitors of RhoA or ROCK are commonly utilized to promote peripheral nerve regeneration [ 6 , 7 ]. However, considering that the drugs used to treat the injured nerve may not just affect neurons but also impact on other cells, and a certain molecule might play diverse roles in different cell types [ 8 10 ]. Hence, we believe that revealing the role of RhoA in different cells is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our team has found several surprising effects of RhoA on Schwann cells, such as RhoA knockdown depressing Schwann cell’s proliferation, migration, and myelination, and the typical downstream molecule ROCK does not contribute to some effects of RhoA on Schwann cells. For example, RhoA regulates Schwann cell’s differentiation through JNK pathway, while influencing its proliferation by regulating AKT pathway [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also reported that active YAP/TAZ is not required for injury-induced SC proliferation in the early phase of nerve regeneration [ 24 ]. Furthermore, Y-27632 treatment does not alter SC proliferation rates because RhoA regulates SC proliferation through AKT rather than ROCK signaling [ 75 ]. When compared to our results, it is promising to transiently suppress ROCK or YAP/TAZ activity at the onset of nerve regeneration, which may help promote SC regenerative ability without impacting SC proliferation rates.…”
Section: Discussionmentioning
confidence: 99%